The Relationship Between the Duration of 3-Month Injectable Hormonal Contraceptive Use and Blood Pressure in Women of Childbearing Age at the Siti Nur Faizah PMB, Jember Regency - Arifah Zannuba Chofsah; Jenie Palupi; Eni Subiastutik (Sean Institute, 2025)
Injectable contraception is a type of hormonal contraception that has advantages and disadvantages, one of the effects is increased blood pressure and weight if used for a long period of time. Active family planning users in Jember Regency on condom contraception are (1,343) people, implants (19,778) people, injectable contraception (165,626) people, pills (67,522) people (BPS East Java Province Statistics East Java, 2022). Method: This study design uses observational analytics with a cross-sectional approach. The study population All women of childbearing age who use 3-month hormonal contraceptive injections with a random sampling technique, namely 48 respondents. Data collection using a questionnaire. Data analysis with the Chi-Square test. Results: 52.1% Using 3-month hormonal contraceptive injections with a duration of <24 months, 58.3% of respondents experienced an increase in normal blood pressure. There is a relationship between the duration of use of 3-month hormonal contraceptive injections and increased blood pressure, obtained aρ-value = 0.001 <α0.05. Conclusion: The duration of use of 3-month hormonal contraceptive injections can cause increased blood pressure in women of childbearing age, women of childbearing age prefer contraceptive methods that suit their needs and consult health workers to avoid risk factors.